Optimalisasi Pengajian Rutin Sebagai Upaya Pemberdayaan Masyarakat Desa Banjarsari Kec. Enggano Kab. Bengkulu Utara - Mainaki, Taufik Ruudyan; Fitriyani, Diah; Sari, Resti Indah Puspita; Afifa, Ira Nur; Murniati, Diana Sri; Aulia, Zumrotul; Alamsyah, Zaid Raihan; Anggraini, Nindiya Putri; Rizseta, Franda; Suparmi, Suparmi; Mostofa, Padly (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
Regular recitation in Banjarsari Village, Enggano District, North Bengkulu Regency has a strategic role in community empowerment. UINFAS Bengkulu KKN students, Group 6 Batch 3, play an active role in optimizing the recitation activities through mentoring. The implementation of this activity involves several stages, namely an initial meeting with the recitation committee, active involvement in each recitation session, and post-recitation evaluation. The results of this mentoring method include an increase in community religious knowledge and strengthening social solidarity. The evaluation showed that the program succeeded in improving the community's religious understanding and creating stronger social ties among the recitation participants. It is hoped that this mentoring method can continue to be applied and developed to improve the quality of routine recitation in the future, as well as strengthen the role of recitation as a means of community empowerment. This routine recitation, apart from being a means of learning religion, also plays an important role in shaping the character of a more religious and empowered community. Through this activity, KKN students not only learn to apply the knowledge they have gained but also contribute significantly to the empowerment of the Banjarsari Village community